影响白癜风患者生活质量的因素:全国性研究. (22nd January 2018) - Bae, J.M.; Lee, S.C.; Kim, T.H.; Yeom, S.D.; Shin, J.H.; Lee, W.J.; Lee, M.‐H.; Lee, A.‐Y.; Kim, K.H.; Kim, M.B.; Park, C.J.; Lee, S.H.; et al.
Abstract : Linked Article: Bae et al. Br J Dermatol 2018;178 :238–244